Maintaining two decades of power amplifier bandwidth. Issue 20 (1st October 2015) - Setzer, C.; Cochran, D.
Abstract : Although several companies are selling MMIC distributed amplifiers with indications of two or more decades of usable bandwidth, the data has been difficult to implement in a practical amplifier design. Suppliers generally make coupling C's and bias tee's an external part of the MMIC measurement system and their losses are often removed (de‐embedded) from the published data. Application engineers for even the largest vendors often seem to be unaware of how to practically achieve the bandwidth properties inherent to their devices, which requires simultaneous optimisation of both the high‐ and the low‐frequency response. In this reported work using the axiomatic design approach allows systematically eliminating bandwidth bottlenecks and obtaining greater than two decades of bandwidth in a high‐power module. The provided example uses an internally matched GaN distributed MMIC, but the same techniques are useful in many other configurations.